2022
DOI: 10.1002/ep.14028
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigations on the performance of solar cooker using nichrome heating coil—Photovoltaic with microcontroller PIC 16F877A

Abstract: In this article, a solar cooker with photovoltaic was developed and manufactured, which offers an electrical emergency power supply and a nichrome heating element in order to be able to cook even on cloudy days and nights. An effective charge controller is made with the microcontroller PIC 16F877A to charge and power the nichrome heating element wound on the cooking vessel. The charge controller

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 25 publications
0
1
0
Order By: Relevance
“…In conventional heat transfer fluids, nanofluids are created by scattering and steadily suspending nanoparticles, whose size in typically in the range of 1 to 100 nm [14]. Researchers demonstrated that nanofluids have superior heat conductivity and stronger convective heat transfer capability than base fluids through their usage in solar cooker applications [7,[15][16][17]. Many studies investigated the nanofluid-based PTC experimentally and numerically.…”
Section: Introductionmentioning
confidence: 99%
“…In conventional heat transfer fluids, nanofluids are created by scattering and steadily suspending nanoparticles, whose size in typically in the range of 1 to 100 nm [14]. Researchers demonstrated that nanofluids have superior heat conductivity and stronger convective heat transfer capability than base fluids through their usage in solar cooker applications [7,[15][16][17]. Many studies investigated the nanofluid-based PTC experimentally and numerically.…”
Section: Introductionmentioning
confidence: 99%
“…When this is not the case, the Direct Current (DC) produced by the panels is usually directly consumed, sparing the inverter, e.g., Simon Prabu [28], and Atmane [29] among others. There are commercial devices that rely on charging a local battery for later use while eventually supplying a load.…”
Section: Introductionmentioning
confidence: 99%